Determinants of Birth Asphyxia among Preterm Newborns in Ethiopia: A Systematic Review and Meta-analysis of Observational Studies Protocol - Tadesse, Abay Woday; Muluneh, Muluken Dessalegn; Aychiluhm, Setognal Birara; Mare, Kusse Urmale; Wagaw, Gebeyaw Biset (BMC, 2022)
Background: Birth asphyxia accounted for nearly 50% of neonatal mortality in Sub-Saharan African countries. This scenario has been worst in Ethiopia where every two out of three deaths attributed to birth asphyxia. Moreover, stud ies conducted in Ethiopia were highly variable and inconclusive to estimate the pooled prevalence and determinants of perinatal birth asphyxia among preterm babies. Objective: This study aimed to estimate the pooled prevalence of birth asphyxia and its determinants among pre term newborns in Ethiopia. Methods: The protocol for this review is registered at PROSPERO with registration number CRD42020158224. A comprehensive online databases (PubMed, HINARI, Scopus, EMBASE, Science direct, and Cochrane library database), Google Scholar, African Journals online, other gray and online repository accessed studies will be searched using diferent search engines. In addition, maternity and infant care databases uploaded at Ethiopian Health Develop ment Journal and Ethiopian Journal of Health Sciences will be searched until 30 June 2020. Newcastle-Ottawa Quality Assessment Scale (NOS) will be used for critical appraisal of studies. Three reviewers will screen all retrieved articles, conduct data extraction, and then critically appraise all identifed studies. All identifed observational studies reporting the prevalence of birth asphyxia and associated factors among neonates in Ethiopia will be considered. The analysis of data will be done using STATA 11.0. We will demonstrate pooled estimates and determinants of birth asphyxia with efect size and 95% confdence interval. Heterogeneity among the included studies will be assessed through the Cochrane Q test statistics and I2 test. Publication bias will be checked using funnel plot and Egger’s test. Finally, statis tical signifcance level will be declared at a p value of less than 0.05. Discussion: The result from this systematic review will inform and guide health policy planners to invest limited resources on maternal and neonatal health. Furthermore, it will be a stimulus for future cumulative meta-analysis researchers in developing nations.
© The Author(s) 2022. Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/. The Creative Commons Public Domain Dedication waiver (http://creativeco mmons.org/publicdomain/zero/1.0/) applies to the data made available in this article, unless otherwise stated in a credit line to the data.
Keywords: Preterm Newborns; Meta-analysis; Birth asphyxia; Difficulty of breathing at birth; Determinants; Ethiopia